APPLYING TALKING CHIPS METHOD IN TEACHING - Hamid Ismail; Saiful; Rina Asrini Bakri; Sumirna (Almeera Education, 2022)
The purpose of this study is to understand how the use of Method Talking Chips can increase the capacity of students boarding students at the first-year sole school in Kabupaten Gowa. First grade students of SMAN 13 Gowa year 2019/2020 is the focus of this essay. There are 247 participants who make up the seven classes, which are the exact class (X IPA 1), which has 33 participants, the exact class (X IPA 2), which has 34 participants, and the exact class (X IPA 3), which has 37 participants. X Social 1) was composed of 36 students, while X Social 2 was composed of 34 students. The 35 students who make up the social class (X social 3). The 38 women who make up the social class (X social 4). Purposive sampling techniques were used in this study. Class that is advertised as a secondary school. The recording is used to analyze the language that was spoken by the students. The total score for all participants in the pre-test can be interpreted as being 6.8. In the post-test, the mean scores of students' fluency and the mean scores of students' comprehension were respectively 4.03 and 3.68. The total number of average students at the post-test was 7.71. By comparing the total number of participants at the pre- and post-tests, it can be seen that the post-test had a higher total number of participants than the pre-test. With other words, it can be said that 7.71>6.8. It is possible to demonstrate that using the chip-based speaking method, students understanding and speaking fluency both significantly increase.